Assessment of the Interaction Conditions of I‐shaped Cross‐Sections. Issue 2 (1st September 2021) - Ludwig, Christian
Abstract: In this research, the interaction conditions for double‐symmetric I‐sections without fillets are analysed. Interaction conditions are necessary for the determination of plastic load‐bearing capacity, which is preferred over elastic load‐bearing capacity for economic reasons. In literature, standards and current research projects, different interaction conditions for My, Mz and Mω are available. However, analyses of their accuracy are missing. This research intends to determine the deviations of each interaction condition using numerical approaches. The interaction conditions are verified on the basis of extensive parameter studies. This study shows that the solutions available in EN 1993‐1‐1 and prEN 1993‐1‐1 lead to uneconomical results. Furthermore, for the application of the interaction condition according to EN 1993‐6 certain limits have to be considered to avoid a non‐conservative design. In this paper, the new extended exponent method is presented. This method is a simple, economical and conservative solution.